2019
DOI: 10.1002/hed.26027
|View full text |Cite
|
Sign up to set email alerts
|

Variations in concerns reported on the patient concerns inventory in patients with head and neck cancer from different health settings across the world

Abstract: Background:The aim was to collate and contrast patient concerns from a range of different head and neck cancer follow-up clinics around the world.Also, we sought to explore the relationship, if any, between responses to the patient concerns inventory (PCI) and overall quality of life (QOL). Methods: Nineteen units participated with intention of including 100 patients per site as close to a consecutive series as possible in order to minimize selection bias.Results: There were 2136 patients with a median total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 17 publications
5
33
1
Order By: Relevance
“…Patients’ concerns were mostly regarding their physical status, treatment-related issues and emotional domains, specifically on ‘fear of cancer coming back’, ‘dental health’, ‘chewing’, ‘dry mouth’, ‘sore mouth’, ‘swallowing’, ‘cancer treatment’, ‘diet restriction’, ‘shoulder’, ‘speech/voice’ or ‘fear of adverse events’. These concerns concurred with other studies [ 8 , 53 , 54 ]. Although differences in the ranking order of concerns were noted in comparison with recent findings by Rogers et al [ 53 ], dental health and oral functions constituted the six most frequent patient concerns, very much related to the early phase of post-treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients’ concerns were mostly regarding their physical status, treatment-related issues and emotional domains, specifically on ‘fear of cancer coming back’, ‘dental health’, ‘chewing’, ‘dry mouth’, ‘sore mouth’, ‘swallowing’, ‘cancer treatment’, ‘diet restriction’, ‘shoulder’, ‘speech/voice’ or ‘fear of adverse events’. These concerns concurred with other studies [ 8 , 53 , 54 ]. Although differences in the ranking order of concerns were noted in comparison with recent findings by Rogers et al [ 53 ], dental health and oral functions constituted the six most frequent patient concerns, very much related to the early phase of post-treatment.…”
Section: Discussionsupporting
confidence: 93%
“…The median number of three concerns selected by patients in the present study was lower than the latest PCI variation study by Rogers et al [53], which reported with a median (IQR) of 5 (2-10) concerns (range of 0 to 48 items) [53]. In addition, a lower proportion of patients in the present study selected six or more concerns compared to nearly half in the latter study [53].…”
Section: Discussioncontrasting
confidence: 80%
“…Although extensively used globally, its focus of use has been with curative head and neck cancer patients, but it has potential to be adapted. 71 Further research into which ‘screening’ tool or method would be most appropriate for initiating palliative care referral for head and neck cancer patients seems pertinent. Furthermore, clarity about how best to incorporate specific staging indicators for those recognised to be ‘high risk’ 72 in additional to individual patient needs would seem beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…The fields of application of telemedicine are multiple: in the first management of maxillofacial traumas, in teleradiology, in follow-up visits and numerous others [8][9][10][11][12][13]. Another useful application might be the administration of a survey before the visit, in order to better focus the attention on the points considered critical by the patient during the visit [14,15]. There is considerable room for improvement and action should be taken in this direction.…”
Section: Discussionmentioning
confidence: 99%